1987
DOI: 10.1007/bf00403035
|View full text |Cite
|
Sign up to set email alerts
|

Photorespiratory N donors, aminotransferase specificity and photosynthesis in a mutant of barley deficient in serine: glyoxylate aminotransferase activity

Abstract: A mutant of Hordeum vulgare L. (LaPr 85/84) deficient in serine: glyoxylate aminotransferase (EC 2.6.1.45) activity has been isolated. The plant also lacks serine: pyruvate aminotransferase and asparagine: glyoxylate aminotransferase activities. Genetic analysis of the mutation strongly indicates that these three activities are all carried on the same enzyme protein. The mutant is incapable of normal rates of photosynthesis in air but can be maintained at 0.7% CO2. The rate of photosynthesis cannot be restored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 24 publications
1
52
0
1
Order By: Relevance
“…Studies on various photorespiratory mutants have not consistently agreed on the way that potential CO 2 release steps may be altered. Studies with a barley mutant deficient in Ser:glyoxylate aminotransferase demonstrated significantly elevated release of labeled CO 2 from exogenously supplied glyoxylate (Murray et al, 1987). In contrast, a HPR barley mutant (Murray et al, 1987) showed little evidence for an increased CO 2 release, even though there was considerable photosynthesis in air.…”
Section: Photorespiratory Metabolitesmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies on various photorespiratory mutants have not consistently agreed on the way that potential CO 2 release steps may be altered. Studies with a barley mutant deficient in Ser:glyoxylate aminotransferase demonstrated significantly elevated release of labeled CO 2 from exogenously supplied glyoxylate (Murray et al, 1987). In contrast, a HPR barley mutant (Murray et al, 1987) showed little evidence for an increased CO 2 release, even though there was considerable photosynthesis in air.…”
Section: Photorespiratory Metabolitesmentioning
confidence: 94%
“…Studies with a barley mutant deficient in Ser:glyoxylate aminotransferase demonstrated significantly elevated release of labeled CO 2 from exogenously supplied glyoxylate (Murray et al, 1987). In contrast, a HPR barley mutant (Murray et al, 1987) showed little evidence for an increased CO 2 release, even though there was considerable photosynthesis in air. A barley mutant deficient in catalase (Kendall et al, 1983) showed no evidence for increased CO 2 release, while an Arabidopsis transgenic plant with antisense reduction in the levels of the 2-oxoglutarate/ malate translocator (Schneidereit et al, 2006) showed a significant increase in G.…”
Section: Photorespiratory Metabolitesmentioning
confidence: 94%
“…AGT1, localized in peroxisomes of Arabidopsis, is a key photorespiratory enzyme that has the highest specific activity with the Ser:glyoxylate aminotransferase reaction (Liepman and Olsen, 2001). Previous studies have shown that plant mutants lacking Ser:glyoxylate aminotransferase activity were not viable when grown in the atmospheric condition but survived when photorespiration was suppressed by increasing CO 2 concentration in a growing environment (Somerville and Ogren, 1980;Murray et al, 1987). The enhancement of photorespiratory pathway severely diminishes the efficiency of CO 2 assimilation and the yield of C 3 -crops (such as rice, wheat, soybean [Glycine max], and potato [Solanum tuberosum]) and improvement of crop yield of C 3 plants can be achieved in an atmosphere containing elevated CO 2 level, resulting in increased CO 2 assimilation and suppressed photorespiration (Reynolds et al, 2000).…”
Section: Diverse Classes Of Up-regulated Genes Identified In the Hybrmentioning
confidence: 99%
“…More recently, in transformed tobacco, the underexpression of catalase has been shown to be associated with an increased CO # compensation point, whereas the reverse was observed in plants overexpressing the enzyme (Brisson et al, 1998). By contrast, labelling experiments in the catalasedeficient barley mutant produced no evidence for increased CO # release in conditions promoting high rates of photorespiration (Kendall et al, 1983), even though increased CO # release can occur in barley lacking sufficient aminotransferase activity to keep pace with glyoxylate production (Murray et al, 1987). Further work is required to resolve the apparent discrepancy between the results in barley and tobacco (Kendall et al, 1983 ;Brisson et al, 1998).…”
Section: Catalase and Foliar Hmentioning
confidence: 99%